Numerical Feasibility Study on Ground Deformation Caused by Enlargement of Shallow Box Tunnel - Yohan Cha; Gye-Chun Cho; Eun-soo Hong (Society for Mining, Metallurgy & Exploration, 2016)
"Rapid population growth and scarcity of space have led many developed cities to bury supply facilities. In line with this, utility tunnels have been employed in Korea since the 1970s. However, approximately 70% of structures were installed more than 20 years ago, in response to the issue of ageing, tunnel enlargement has been proposed. The aim of this study is to investigate geo-mechanical behavior due to tunnel enlargement. Tunnel enlargement methods have been researched to suggest a optimal method. A finite element analysis is conducted to evaluate ground behavior by the expansion of internal space. Vertical displacement and settlement trough width are investigated according to ground stiffness and different enlargement size. It was determined that displacement is affected by the enlargement size and ground stiffness. Based on the deformation results obtained from the numerical analysis, it is possible to predict ground behavior and stability upon tunnel enlargement. INTRODUCTION Various infrastructures such as electric lines, communication lines, gas pipes, and water pipes are jointly accommodated by utility tunnels. These utility tunnels improve the aesthetics of urban areas and help ensure stable supply. The first utility tunnel in Korea was adopted in 1978 and new tunnels are still being installed with the development of new suburb cities. Nevertheless, about 70% of the utility tunnels were installed over 20 years ago and they are still being used through ongoing repair. Moreover, 90% of utility tunnels were installed before 1995. With aging of the nation’s utility tunnels various problems such as concrete deterioration and scarcity of capacity have arisen. As solution, reconstruction has been considered. Reconstruction can enlarge space and improve the performance by replacing existing structures. For reconstruction, two routes have been proposed: underground excavation and cut and cover. In order to avoid traffic problems caused by road occupation and civil appeals during construction projects, underground excavation is the more attractive option. Tunnel enlargement methods have been classified (Seo et al., 2008; An et al 2013) and major considerations during tunnel enlargement have been outlined (Beak et al., 2007). Enlargement construction cases on road tunnels around the world were introduced (Kim et al., 2012) and the deformation curve during tunnel expansion was proposed to investigate the range of protection that should be offered (Kim et al., 2008; Beak et al., 2011). However, tunnel enlargement technology is limited to road tunnels and railway tunnels. Hence, a study on shallow box tunnel enlargement is required for practical application."